SISTEM AKUNTANSI PENGGAJIAN DRIVER PADA PT. JAYA SEMPURNA DELAPAN DI SAMARINDA - Yustika Manurung (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
The purpose of this study was conducted to find out how the payroll driver accounting system at PT. Jaya Sempurna Eight in Samarinda. In this research the method used is descriptive method. Data obtained through interviews, documentation, and literature study. The results of this study indicate that the payroll accounting system at PT. Jaya Sempurna Eight has been going well enough. related functions, documents used, accounting records used, and the network of payroll procedures in the company are quite good and in accordance with the theory so that the existing payroll system in the company can continue to run well and the company has also done the division of tasks and separation of functions in accordance with its parts. Thus minimizing the occurrence of fraud due to overlapping functions in the payroll system. It's just that in the personnel section in making a pull list (SP2) the personnel section driver still does it manually using book records so that in processing the pull list (SP2) it takes a long time and errors in the calculation of the amount of pull often occur causing errors in the calculation of wages. Therefore it is necessary to repair the system by using a computerized system in making a pull list (SP2) driver so it makes it easier for the personnel in making a pull list.